2016
DOI: 10.1007/s41233-016-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

QoE beyond the MOS: an in-depth look at QoE via better metrics and their relation to MOS

Abstract: Abstract-This

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 30 publications
3
78
0
1
Order By: Relevance
“…However, other QoE metrics (like median, quantiles, etc.) may be especially of interest for service providers [10] which may be reflected by Q. Typically, the QoE of the entire session per user is modeled.…”
Section: Definition Of the Qoe Fairness Index A Notionmentioning
confidence: 99%
“…However, other QoE metrics (like median, quantiles, etc.) may be especially of interest for service providers [10] which may be reflected by Q. Typically, the QoE of the entire session per user is modeled.…”
Section: Definition Of the Qoe Fairness Index A Notionmentioning
confidence: 99%
“…We must emphasize that the approach used here for simulating user diversities is supported by the literature [6]. It is based on real subjective data, and has been shown to lead to very good approximations.…”
Section: A Two Users Scenario: Optimal Qoe Resource Assignmentmentioning
confidence: 91%
“…While the majority of studies to-date addressing QoE estimation models rely on MOS values derived from subjective data, other studies have shown that different metrics beyond MOS may be of potential interest to service/network providers [6]. Statistical measures providing insight into score distributions and quantiles give providers a clearer view of how quality is actually perceived by the user population, rather than estimating the quality as perceived by an "average" user.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations